2021
DOI: 10.7759/cureus.19788
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Retrograde Trans-Synaptic Degeneration of Ganglion Cells and Optical Coherence Tomography Angiography Following Ischemic Stroke

Abstract: Objective Following nerve injury, the projection of posterior visual pathway lesions into the macular ganglion cell layer (GCL) region indicates retrograde trans-synaptic degeneration (RTSD) as a mechanism of functional damage. Our purpose is to assess GCL damage and the impacts of ischemic brain lesions affecting the visual pathway on macular microvascularization in patients with stroke. Methods In a case-control study, we examined 15 ischemic stroke patients who sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Multiple studies have found significant changes in both the SRL and DRL in patients with stroke. A case-control study with 15 ischemic stroke patients found that VD was significantly reduced at the level of all vascular plexuses in stroke patients [53]. Additionally, a study by Liang et al [54] in 2022 found that the VD in the SCP and DCP was significantly reduced in ischemic stroke patients compared to those in the control [54].…”
Section: Atherosclerotic Diseasementioning
confidence: 97%
“…Multiple studies have found significant changes in both the SRL and DRL in patients with stroke. A case-control study with 15 ischemic stroke patients found that VD was significantly reduced at the level of all vascular plexuses in stroke patients [53]. Additionally, a study by Liang et al [54] in 2022 found that the VD in the SCP and DCP was significantly reduced in ischemic stroke patients compared to those in the control [54].…”
Section: Atherosclerotic Diseasementioning
confidence: 97%
“…Additionally, DRCP VD and vascular area (VA) was found to be reduced, along with a decrease in the outer retina layer VD. The total of RPC, SCP, and ICP VA was reduced [238]. Liang et al found that GCC and RNFL thickness were reduced, and SRCP, DRCP, and RPC VD were generally lower in ischemic stroke patients compared to HC [239].…”
Section: Ischemic Stroke Patient Vs Hcmentioning
confidence: 98%
“…The regression analyses confirmed that OCT-A was able to distinguish stroke patients from controls with good sensitivity and specificity. Molero-Senosiain et al performed OCT-A in stroke patients with ischemic lesions affecting the visual pathway and in a healthy control group [ 55 ]. All included stroke patients had partial visual field defects as a consequence of the ischemic attack.…”
Section: Oct-a Findings In Neurological Diseasesmentioning
confidence: 99%
“…Compared to the control group, the vessel density was reduced in all vascular plexuses in the macular and peripapillary regions. The authors do not report more pronounced microvascular changes in areas corresponding to the visual field defects, but the thickness of the GCL correlated with the visual field defects [ 55 ].…”
Section: Oct-a Findings In Neurological Diseasesmentioning
confidence: 99%